Effect of Luminal Angiotensin II Receptor Antagonists on Proximal Tubule Transport - Quan, Albert (1999)
The proximal tubule can endogenously synthesize and secrete luminal angiotensin II at a concentration approximately 100- to 1000-fold higher than that in the systemic circulation. We have recently shown that this endogenously produced and luminally secreted angiotensin II regulates proximal tubule volume reabsorption, which is a reflection of sodium transport within this segment. In this study, we use in vivo microperfusion of angiotensin II receptor antagonists into the lumen of the proximal tubule to examine the role of the luminal AT(1) and AT(2) receptor in the regulation of volume reabsorption. Systemically administered (intravenous) AT(1) and AT(2) receptor antagonists, acting through basolateral angiotensin II receptors, have previously been shown to inhibit proximal tubule transport. Luminal perfusion of 10(−6) mol/L Dup 753 (AT(1) antagonist) and 10(−6) mol/L PD 123319 (AT(2) antagonist) decreased proximal tubule volume reabsorption from 2.94 ± 0.18 to 1.65 ± 0.18 and 1.64 ± 0.19 nL/mm · min, respectively, P < .01. Luminal perfusion of 10(−4) mol/L CGP 42112A, another AT(2) antagonist, similarly decreased volume reabsorption to 1.32 ± 0.36 nL/nm · min, P < .01. The inhibition of transport with AT(1) and AT(2) antagonist was additive, as luminal perfusion of 10(−6) mol/L Dup 753 plus 10(−6) mol/L 123319 resulted in a decrease in volume reabsorption to 0.41 ± 0.31 nL/mm · min, P < .001 v control, P < .05 v Dup 753, and P < .01 v PD 123319. These results show that endogenously produced angiotensin II regulates proximal tubule volume transport via both luminal AT(1) and AT(2) receptors.